Isotrias martelliana sp. n. (Lepidoptera Tortricidae) from Pollino mountaines (Italy) (Bollettino di zoologia agraria e bachicoltura, 2024)
Isotrias martelliana a new species of Tortricidae is described. In the male genitalia martelliana is dose to I. joannisana (Turati) from Italy. The differences between the two species are in the coloration of forewings, in the shape of valva and number of spines in the end of sacculus ventrally, which in martelliana is the only one.
Keywords: Isotrias martelliana; Lepidoptera Tortricidae; new species